The Effect of Balanced Nutrition Education Using Written Brainstorming Methods Accompanied by Online Games on Adolescent Girls at MTs Annajah Jakarta - Zahira, Zahra (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Lack of knowledge and attitudes about balanced nutrition in adolescent girls can lead to nutritional problems such as underweight, Chronic Energy Deficiency, anemia, obesity, and overnutrition. One of the attempts to improve knowledge and attitudes is through nutrition education with the written brainstorming method accompanied by online games. The aim of this research is to determine the effect of balanced nutrition education using written brainstorming methods accompanied by online games on knowledge and attitudes in adolescent girls. The research design is quasi-experimental with a two-group pretest-posttest design. Total sample of 85 people selected by random sampling. The instruments used were knowledge test sheet and attitude questionnaire. Statistical analysis used was an Independent T test. The results showed that using the written brainstorming method accompanied by online games had an effect on the knowledge and attitude of balanced nutrition in MTs Annajah Jakarta students with a significance value for knowledge (p=0.000) and the value for attitude (p=0.000). The suggestion given by researchers is the use of learning media as an illustrative aspect so that nutrition education activities are more effective and motivate students.